Respuesta :
[tex]D:x\not=0 \wedge 1+x^2\not=0\\
D:x\not =0\\\\
\dfrac{1}{x}-\dfrac{2x}{1+x^2}=0|\cdot x(1+x^2)\\
1+x^2-2x^2=0\\
1-x^2=0\\
x^2=1\\
x=-1 \vee x=1
[/tex]
(1/x) - (2x/(1+x^2)) = 0
Multiply by x(x^2+1)
1(x^2+1)+(−2x)(x)=0x(x2+1)
−x^2+1=0(Simplify both sides of the equation)
−x^2+1−1=0−1(Subtract 1 from both sides)
−x^2=−1
−x^2−1=−1−1(Divide both sides by -1)
x^2=1
x=ñ1(Take square root)
x=1 or x=−1
Multiply by x(x^2+1)
1(x^2+1)+(−2x)(x)=0x(x2+1)
−x^2+1=0(Simplify both sides of the equation)
−x^2+1−1=0−1(Subtract 1 from both sides)
−x^2=−1
−x^2−1=−1−1(Divide both sides by -1)
x^2=1
x=ñ1(Take square root)
x=1 or x=−1